Physicochemical Characteristics of Cocoa Nibs (Theobroma cacao L) by Differences in Temperature and Roasting Time - Elianarni, Dahlia; Fadilatulail MI, Annisa; Harini, Noor; Manshur, Hanif Alamudin (Jurnal Teknologi Pangan, 2025)
Cocoa is one of the superior commodities in Indonesia. The area for growing cocoa beans reaches 1,651,539 hectares. In recent years, there has been a significant decline in cocoa productivity. This is influenced by the potential of clones starting to decline and pest attacks damages cocoa pods resulting in reduced productivity in each season. This research aims to determine the physicochemical components of cocoa seeds in Mojokerto City. Seed quality test parameters include water content test, grade, fat, pH, polyphenols, yield, and color intensity. The research method used was Group Randomized Design which was tested using ANOVA and Continue with Duncan Multiple Range Test (DMRT). The research results show that at parameters water content (3.48%-5.54%), fat content (36%-62%), pH content (4.96-5.54) and color intensity there is an interaction while with the yield parameters and polyphenols, there is no interaction.